2006
DOI: 10.4161/cbt.5.11.3302
|View full text |Cite
|
Sign up to set email alerts
|

Furanonaphthoquinones cause apoptosis of cancer cells by inducing the production of reactive oxygen species by the mitochondrial voltage-dependent anion channel

Abstract: The mitochondrial production of reactive oxygen species has been implicated in the anticancer activity of furanonaphthoquinone. However, the mechanism of the activation remains elusive. In the current study, we found that treatment of HeLa cells with 2-methyl-5(or -8)-hydroxy-furanonaphthoquinone (FNQ13) induces mitochondrial swelling, followed by apoptosis. This toxic effect of FNQ13 was reduced by the radical scavengers alpha-tocopherol and trolox. Cytochemical experiments in isolated mitochondria showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 24 publications
0
76
0
2
Order By: Relevance
“…Consistent with this finding, VDAC1-siRNAs lower the ROS as well as cell death induced by FNQ13 [61], and downregulation of VDAC1 reduces apoptosis induced by cisplatin [67]. Conversely, VDAC1 downregulation does not affect cellular responsiveness to inducers of physiological apoptosis like STS.…”
Section: Vdac1 As a Selective Mediator Of The Response To Oxidative Smentioning
confidence: 53%
See 1 more Smart Citation
“…Consistent with this finding, VDAC1-siRNAs lower the ROS as well as cell death induced by FNQ13 [61], and downregulation of VDAC1 reduces apoptosis induced by cisplatin [67]. Conversely, VDAC1 downregulation does not affect cellular responsiveness to inducers of physiological apoptosis like STS.…”
Section: Vdac1 As a Selective Mediator Of The Response To Oxidative Smentioning
confidence: 53%
“…In general, VDACs have often been considered as mediators of apoptosis induced by ROS [37,[57][58][59][60]. Recently, Simamura et al [61] demonstrated that the anti-cancer activity of the furanophtoquinone FNQ13 was potentiated by overexpression of VDAC1 and the mitochondrial production of ROS. This finding confirms a previous report from our lab where it was demonstrated that plasma membrane VDAC may act as a transmembrane oxidoreductase using the cytoplasmic NADH as the reducing species [62].…”
Section: Vdac1 Ros and Selenite: Potential Mechanisms Of Ptp Openingmentioning
confidence: 99%
“…Unfortunately these authors did not consider that in the outer mitochondrial membrane there are three different VDACs. Since dextran sulfate acts as a kind of clog upon the pore and since the VDAC isoforms are structurally very similar, it is very probable that the overall effect measured for example in [41] was not specific of VDAC1 but possibly the sum of the effect of the isoforms. In the literature there are systemic surveys of ROS-dependent chemical modifications of the yeast proteome and it was shown that VDAC was usually involved.…”
Section: Vdacs and Rosmentioning
confidence: 99%
“…It adjusts cell oxidation-reduction reactions and participates in apoptosis through regulating the permeability of mitochondrial membrane under the influence of proapoptotic Bax and Bak proteins or antiapoptotic Bcl-xL protein (91,92). VDAC1 has been reported to be overexpressed in several cancer cells (93,94), however, the suggested roles of this molecules have been inconsistent in several studies. For example, in studies by Simamura et al, overexpression of VDAC1 in cancer cells was reported to increase the sensitivity of cancer cells to quinine antitumor drugs (93)(94)(95).…”
Section: Tumor Stage ------------------------------------------------mentioning
confidence: 99%
“…VDAC1 has been reported to be overexpressed in several cancer cells (93,94), however, the suggested roles of this molecules have been inconsistent in several studies. For example, in studies by Simamura et al, overexpression of VDAC1 in cancer cells was reported to increase the sensitivity of cancer cells to quinine antitumor drugs (93)(94)(95). On the other hand, Pan et al reported that VDAC1 was consistently increased at both the protein and the RNA levels in caboplatinand paclitaxel-resistant ovarian cancer (96).…”
Section: Tumor Stage ------------------------------------------------mentioning
confidence: 99%